Cybersymbiosis: towards a Psychoanalysis of Hybrids (INSÓLITA - Revista Brasileira de Estudos Interdisciplinares do Insólito, da Fantasia e do Imaginário, 2026)
In an effort to ground a way to think about the current deep imbrication between subjectivity and technology, this article aims to analyze some processes of vitalization and potentiation derived from cybernetic culture. Thus, we intend to construct an alternative path to the contemporary critical trend, which generally strives to produce diagnoses and identify discontents, pointing to an emptying and impoverishment of subjectivities today. To counter this bias, without denying its relevance, we will seek to understand what hybridization and cyborg subjectivities are. By reformulating the value that classical psychoanalysis gave to symbiosis, we will construct here the notion that technologies and digital space operate in a prosthetic way, serving as extensions of the body and subjectivity. Combining philosophy, psychoanalysis, anthropology and literature through the concept of cybersymbiosis, we will see that our technological composition is not inherently alienating, but offers possibilities for openness and transformation, as transitional phenomena coupled with subjectivation.